Profile of Hand Compartment Syndrome in Dr. Hasan Sadikin General Hospital, West Java, 2008â2012 - Manogaran, Kajendaran; Hidajat, Nucki Nursjamsi; Soenggono, Arifin (Althea Medical Journal, 2015)
Background: Compartment syndrome is a serious disorder caused by elevated pressure in a muscle compartment that can progress to muscle and nerve damage. This disorder can happen to anyone but more frequently in young adults. The occurrence frequency of hand compartment syndrome is relatively low. The aim of this study is to identify the profile of compartment syndrome in patients handMethods: A descriptive study was perfomed to 15 cases that were collected from medical records from 2008-2012, in Dr. Hasan Sadikin General Hospital. The profile of the case consisted of age, sex, symptoms and signs, etiology, facsiotomy schedule after admission, length of stay and patientâs outcome. The collected data were presented using tables.Results: The study showed that 12 out of 15 cases were males and 7 out of 15 cases were 20â39 years oldpatients. The common clinical findings were swelling, pain, limited range of motion and normal sensibility. The faciotomy procedure was conducted 1 day after the admission with length of stay more than 1 week. The patients condition were improved after operation. Conclusions: Hand compartment syndrome is a rare case, mostly affects younger adults and male. Most of the symptoms and signs are swelling, limitation of movement, pain in the location area with normal sensibility. The faciotomy procedure is conducted 1 day after admission. The length of stay is more than 1 week with an improved outcome. [AMJ.2015;2(4):497â501]Â DOI:Â 10.15850/amj.v2n4.634